CAUSES OF PERINATAL HYPOXIC-ASPHYXIAL LESIONS AND THEIR IMPACT ON THE NERVOUS SYSTEM IN THE ARAL SEA REGION - Allayev Marat Erkinbaevich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
In recent decades, the ecological crisis in the Aral Sea region has had a seriously negative impact not only on the natural environment but also on public health, especially on the health of mothers and newborn infants. The high concentrations of pesticides, heavy metals, saline dust, and other toxic compounds in the atmosphere, water, and soil disrupt oxygen exchange processes in pregnant women. As a result, fetal oxygen deficiency—hypoxia—occurs and becomes one of the main causes of central nervous system damage during the perinatal period